Greetings and farewells as elementary pragmemes of language etiquette - Dubravka Smajić; Irena Vodopija (Pannoniana, 2016)
Greetings are one of the oldest forms of human communication. They can be verbal, verbal/non-verbal and non-verbal communication acts. Greetings are used in direct communication dialogues. This communication usually consists of two components: invocation as a greeting and revocation as a farewell. Together they are commonly referred to as greetings. First and foremost, greetings belong to the category of linguistics and communication. However, they are social and ideological acts, too, thus the acquisition of their accurate and appropriate use is required with respect to communication partners and situation specificity. At different levels of education, higher education institutions included, and particularly those responsible for training of future pre-school and primary teachers, the mission includes promotion of linguistic appropriateness and, subsequently, linguistic politeness. Hence, greeting and farewell as pragmemes of language etiquette are amatter of theoretical and practical interest in the study of linguistic appropriateness.